Plasma retinol and the risk of first stroke in hypertensive adults: a nested case-control study. Issue 2 (9th January 2019) - Yu, Yaren; Zhang, Hao; Song, Yun; Lin, Tengfei; Zhou, Ziyi; Guo, Huiyuan; Liu, Lishun; Wang, Binyan; Liu, Chengzhang; Li, Jianping; Zhang, Yan; Huo, Yong; et al.
ABSTRACT: Background: Identification of novel risk factors is needed to further lower stroke risk. Data concerning the association between plasma retinol concentrations and the risk of stroke are limited. Objectives: We aimed to evaluate the effect of plasma retinol on the risk of first stroke and to examine any possible effect modifiers in hypertensive patients. Methods: The study sample population was drawn from the China Stroke Primary Prevention Trial (CSPPT), using a nested case-control design, including 620 cases with first stroke and 620 matched controls. In the CSPPT, a total of 20, 702 hypertensive patients were randomly assigned to a double-blind, daily treatment with either 10 mg enalapril and 0.8 mg folic acid or 10 mg enalapril alone. The median treatment duration was 4.5 y. Results: There was a significant inverse association between plasma retinol and the risk of first stroke (per 10-μg/dL increment; OR: 0.92; 95% CI: 0.86, 0.97) and first ischemic stroke (OR: 0.92; 95% CI: 0.86, 0.98). When retinol was assessed as quartiles, significantly lower risks of first stroke (OR: 0.64; 95% CI: 0.46, 0.88) and first ischemic stroke (OR: 0.67; 95% CI: 0.46, 0.96) were found in participants in quartiles 2–4 compared with those in quartile 1. Furthermore, a stronger inverse association between plasma retinol and first stroke was observed in participants with baseline total homocysteine (<10 compared with ≥10 μmol/L; P -interaction = 0.049). However, plasma retinol had no significant effect on first hemorrhagic stroke (per 10-μg/dL increment; OR: 0.98; 95% CI: 0.79, 1.18). Conclusions: Our data showed a significant inverse association between plasma retinol and the risk of first stroke among Chinese hypertensive adults. This study was registered at clinicaltrials.gov as NCT00794885.